Epizootic Situation of Feline Bartonella Infection in Eastern Poland - Mazurek, Łukasz (J Vet Res, 2020)
INTRODUCTION: The aim of the study was to establish the prevalence of Bartonella spp. in cats in eastern Poland, and to determine the factors associated with the infection. MATERIAL AND METHODS: PCRs were performed to detect Bartonella DNA in the whole blood of 672 cats from four regions in eastern Poland (the Lublin, Podlasie, Masovian, and Subcarpathian provinces). The association between the previously selected variables and the dependent variable (presence of Bartonella DNA) was investigated using a logistic regression model. RESULTS: The overall prevalence of infection was 40.48%. All PCR positive cats were infected with B. henselae. The living conditions of the animals (free outdoor roaming), mixed breed cats, Subcarpathian region, and absence of tick control were significant risk factors associated with Bartonella infection at a 95% confidence level. CONCLUSION: Cats in eastern Poland appear to be at risk of a bartonellosis epizootic. Factors which seem to impact the likelihood of infection in cats and factors which seem not to impact it have been suggested. We advocate additional research into the ways bartonellosis spreads, its geographical scope, and the factors that favour its development.